2015
DOI: 10.1109/tap.2015.2479242
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Procedure for Planar Leaky-Wave Antennas With Flat-Topped Radiation Patterns

Abstract: International audienceWe describe here an optimization procedure to shape the radiation pattern of planar two-dimensional (2-D) leaky-wave antennas. The structures under investigation are superstrate configurations made by partially reflecting screens (impedances sheets) over a ground plane and excited by open-ended waveguides. The antenna configuration providing the required radiation pattern is obtained by resorting to an ad hoc optimization procedure that minimizes the mean squared error between the target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The superstrates are formed by perforated Rogers 6010LM. The optimisation frequency is set as 13.85 GHz with the requirements of side lobe level S and half 10 dB beam width θ 1 , set in (11), to be −16 dB and 20° respectively. In the optimisation, ε r1 and ε r3 equal to 1. ε r2 and ε r4 are varied from 1.9 to 10.2.…”
Section: Optimisation Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The superstrates are formed by perforated Rogers 6010LM. The optimisation frequency is set as 13.85 GHz with the requirements of side lobe level S and half 10 dB beam width θ 1 , set in (11), to be −16 dB and 20° respectively. In the optimisation, ε r1 and ε r3 equal to 1. ε r2 and ε r4 are varied from 1.9 to 10.2.…”
Section: Optimisation Proceduresmentioning
confidence: 99%
“…For antenna element, such as patch antennas, the pattern synthesis is based on the control of the excitation of resonant modes on the patch [2]. Alternatively, the superstrates using homogeneous dielectric structure (HDS) and/or periodic metal structure (PMS) have been found to be very useful in the pattern synthesis in spatial domain or spectral domain [3][4][5][6][7][8][9][10][11][12][13][14]. In [15], it is shown that these two structures can have same reflection coefficients and may provide almost identical effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, internal stress between high and low refractive index quarter-wave layers also hinders the utility of thin-film devices in high power laser system [2]. Angular filters or spatial filters also received much attention since they are widely used in focus-free system [3,4], solar cell [5,6] and free space optical telecommunication [7,8]. Candidates of angular selectivity schemes include multi-layer thin-film [9][10][11], photonic crystals [12][13][14], volume bragg gratings [15][16][17] and rugate thin-film [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this microstrip TWA design has advantages of simple design schematic, low profile, and easy impedance matching. TWAs have been studied as solutions for gain enhancement of simple radiating sources, side‐lobe level reduction, and radiation pattern reconfiguration . By designing a TWA for RADAR systems in Reference , an effective continuous scanning has been achieved with a small increase in the feeding signal's frequency, thus it is possible to optimize the range and propagation pattern of the radar array, and steer the pattern of antenna for a scanning in time.…”
Section: Introductionmentioning
confidence: 99%